SIMILARITIES BETWEEN MORPHOLOGICAL INDICATORS OF THE STOMACH OF HUMANS AND WHITE-BREEDLESS RATS - Shirinov M.M., Teshaev Sh.J., Eshpulatov E.Y. (PT. Antis International Publisher, 2024)
. Information about the anatomy of the stomach of white-breedless rats is very rare in the scientific literature. The shape, structure, and topography of rat stomachs are significantly different from those of vertebrates, but the same sections as shark stomachs can be found in them. This structure of white rat stomach sections characterizes the sac-like formation of the digestive tract. In the anterior part of the abdominal cavity of rats, on the left side of the midline, there is a hole for the heart between the esophagus and the line of the lesser curvature of the stomach. The liver is located in the small curvature of the stomach and partially covers it. The greater curvature of the stomach touches the caecum and cecum.